Accuracy of Ottawa ankle rules for midfoot and ankle injuries - Yavas, Selen; Arslan, Engin Deniz; Ozkan, Seda; Yilmaz Aydin, Yasemin; Aydin, Macit (Acta Biomedica Atenei Parmensis, 2021)
BackgroundThe management of ankle sprains is common practice in emergency departments. Traditionally, physicians would order radiographs for all ankle injuries although the overall incidence of fractures are less than 15% .  The Ottawa Ankle Rules (OAR) have been developed to predict the necessity of radiographs in acute ankle injuries.Material and MethodThis is a prospective study of consecutive patients aged 16 years or older with acute non-penetrating ankle or foot injuries and who had a radiography of ankle or foot or both.Results499 cases were included in the study. 56.90 % of the patients were male and the median age of the patients was 30 (IQR  22,44).  22.85 % (114/499) of patients with ankle or midfoot injuries had fractures.  The sensitivity, specificity, PPV and NPV of OAR for ankle and midfoot injuries  were 100, 45.26, 26.00, 100 and 100, 43.71, 19.92 and 100 respectively. In this study 792 x rays were ordered from 499 patients. According to OAR 509  (%64.27) of them were indicated whereas 283 (% 35.73) were not. When the weight bearing test is sole criteria 303 ( 38.26%) x rays were obtained to find out three fractures.ConclusionOAR should be safely used in emergency departments. Implantation of this rule prevents patients from unnecessary radiation exposure. It is a reasonable approach to reassess the patient if symptoms not resolve several days later  for avoiding unnecessary x ray exposure when the weight bearing test exist as the only positive criteria.